Characteristics and outcomes for patients with advanced vaginal or vulvar cancer referred to a phase I clinical trials program: the MD Anderson cancer center experience. Issue 1 (May 2015) - Fu, Siqing; Shi, Naiyi; Wheler, Jennifer; Naing, Aung; Janku, Filip; Piha-Paul, Sarina; Gong, Jing; Hong, David; Tsimberidou, Apostolia; Zinner, Ralph; Subbiah, Vivek; Hou, Ming-Mo; et al.
Abstract Background Early-stage vaginal and vulvar cancer can be cured. But outcomes of patients with metastatic disease are poor. Thus, new therapeutic strategies are urgently required. Methods In this retrospective study, we analyzed the clinical outcomes of consecutive patients with metastatic vaginal or vulvar cancer who were referred to a phase I trial clinic between January 2006 and December 2013. Demographic and clinical data were obtained from patients' electronic medical records. Results Patients with metastatic vaginal (n = 16) and vulvar (n = 20) cancer who were referred for phase I trial therapy had median overall survival durations of 6.2 and 4.6 months, respectively. Among those who underwent therapy (n = 27), one experienced a partial response and three experienced stable disease for at least 6 months. Patients with a body mass index ≥30 had a significantly longer median overall survival duration than did those with a body mass index <30 (13.2 months versus 4.4 months, p = 0.04). Preliminary data revealed differences in molecular profiling between patients with advanced vaginal cancer and those with advanced vaginal cancer. Conclusions Metastatic vaginal and vulvar cancers remain to be difficult-to-treat diseases with poor clinical outcomes. The currently available phase I trial agents provided little meaningful clinical benefits. Understanding these tumors' molecular mechanisms may allow us to develop more effective therapeutic strategies than are currently available regimens.